The source basis of the Council of People’s Ministers of the Ukrainian People’s Republic activity research - Hrebeniuk, O. (Вісник Черкаського університету. Серія: Історичні науки, 2017)
Introduction. Since the declaration of independence Ukraine has been trying to decide the issue concerning the establishment and enforcement of the effective work of the executive power. The research of its optimized organization requires the retrospective understanding of the existing national experience, in particular acquired during the Ukrainian revolution (1917-1920). The Central Rada governments - the General Secretariat and the Council of People’s Ministers – tried to solve important questions of international and interior life. The Council of People’s Ministers could agree Ukrainian interests with the Quadruple Alliance, implement the first socioeconomic and cultural reforms inland, resist the invasion of Bolshevik forces and raise the realization of the declared policy during the first months of the German-Austrian forces presence. The research on the activities of the Council of People’s Ministers of the Ukrainian People’s Republic of the Ukrainian Central Rada period is an important approach in history. A special attention need to be paid to the analyses of a wide range of sources for the objective assessment. Purpose. The coverage and fundamental analysis of the scientific sources corpus which represents the basis for the Council of People’s Ministers of the Ukrainian People’s Republic activity research.. Results. The source basis of the research includes archive materials, published collections of documents and materials, memoirs and periodical publications. A significant place among other sources is taken by archive documents and materials deposited in the Central State Archives of Supreme Bodies of Power and Government of Ukraine (TsDAVO of Ukraine). The archive funds are the main source for the research of the pointed topic. Individual funds of ministries and departments are of special interest. Published collections of documents and periodical press of that period are also important groups of sources. Periodical publications have become a reflection of the course of that time events and had a political direction. Conclusion. A detailed analysis of all source groups allows making conclusions about the executive power higher bodies – ministries and departments, the reasons of taking the decisions, achievements and drawbacks of the government work. A thorough investigation of the source basis presents a significant interest for further research on the Council of People’s Ministers of the Ukrainian People’s Republic activity.